Effect of extrusion screw type on properties of recycled glass fiber reinforced liquid crystalline polymer. Issue 2 (23rd August 2014) - Zhang, Shuidong; Tan, Lingcao; Peng, Huaqiao; Liang, Jizhao; Jiang, Guo
Abstract : In this work, when glass fiber reinforced liquid crystalline polymer (GFLCP) was subjected to injection molding once, the recycled GFLCP (RGFLCP) including the scraps and unqualified injection products was granulated by different extruders with varying screw configurations. The glass fibers were observed by SEM and their lengths were calculated by mathematical statistics. In the case of the samples prepared by a single‐screw extruder, the average glass fiber length ( L ¯ ) and the percentage of glass fibers whose length was higher than critical length ( V j ) gradually decreased with the increase of the screw diameter and the ratio of its length to diameter ( L / D ). However, a drastic reduction of L ¯ and V j was observed for the RGFLCP extruded by a twin‐screw extruder. The mechanical, thermal properties, and the shear viscosity of the extruded RGFLCP decreased with the reduction of L ¯ and V j . The extruded RGFLCP prepared with a single screw extruder that was featured with 30 mm screw diameter and 30 L/D obtained the excellent properties with a notched impact strength of 103.4 J/m, tensile strength of 110.2 MPa, and flexural strength of 159.3 MPa. Its initial decomposition temperature ( T −1% ) and heat distortion temperature were 483.1°C and 256.4°C, respectively. POLYM. COMPOS., 37:370–378, 2016. © 2014 Society of Plastics Engineers